Is Weather Index Insurance Sufficient for Smallholder Protection? Emerging Insights from Rainfall-Index Calibration of Maize Crop Losses in Central-West Nigeria - David Olufemi Awolala (Universidade Federal dos Vales do Jequitinhonha e Mucuri, 2020)
Residual impacts from rainfall deficit and failures of traditional crop insurance to protect smallholders are resulting in economic losses threatening Post-Paris adaptation target in Nigeria. Weather index insurance is being considered as a possible pathway towards sharing farmers’ risks. This paper analyzed the reliability of rainfall indexes as proxy for calibrating grain crop losses in designing index-based insurance product for farmers in Central-West Nigeria. Results reveal that two strongest correlated rainfall indexes in the development phase of maize are the second dekad cumulative rainfall climatology and cumulative rainfall below the pre-set 440mm threshold, however it was the third dekad cumulative rainfall climatology and consecutive dry days of total rainfall < daily 2.5 mm threshold in the reproductive stage. There is an overall weak statistical relationship between maize yield and rainfall indexes calibrated in middle savannah belt of Nigeria. This study provides a firsthand empirical validation that rainfall-based indexes are though fairly promising but not sufficiently measure actual farmers’ income losses, hence should not be regarded as a standalone safety-net for protecting smallholders. Careful consideration is required in developing appropriate weather indexes for designing index-based insurance product that will fully captured food crop losses significantly attributed to rainfall deficits, thus facilitate uptake in the semi-arid savannah zone of Nigeria.